Ethnobotany of dye plants in Southern Italy, Mediterranean Basin: floristic catalog and two centuries of analysis of traditional botanical knowledge heritage - A. Prigioniero; A. Geraci; R. Schicchi; M. Tartaglia; D. Zuzolo; P. Scarano; M. Marziano; A. Postiglione; R. Sciarrillo; C. Guarino (BMC, 2020)
Abstract Background Since ancient times, man has learned to use plants to obtain natural dyes, but this traditional botanical knowledge (TBK) is eroding. In the late, during, and the early 1800s, there was an increase in research related to dye species, and this allowed the development of industry and economy in rural contexts of Southern Italy. Today, dyes are mainly obtained from synthetic products, and this leads to risks for human health related to pollution. Methods Starting from the literature, three catalogs of the dyeing species (plants, algae, fungi, and lichens) used in the Mediterranean Basin and mainly in Southern Italy have been created. Percentages of parts used and colors extracted from species have been recorded and analyzed. The plant species present in the catalogs have been verified in the territories of Southern Italy, and the data have been registered. An ethnobotanical survey was conducted, in the region of Southern Italy, to verify the erosion level of traditional botanical knowledge, linked to the ethnobotanical dyeing, over time. Results A total of 524 species were recorded among plants, algae, fungi, and lichens, and related parts used and extracted pigments. Most uses concern the stems and leaves, and the most frequent color is yellow. From the on-field survey operations, 283 plant species have been verified. These represent 64.31% of the species reported in the flora of the dye plants produced. The results, from the ethnobotanical survey, show that only 8.6% of TBK remained in the collective memory. Conclusions This catalog is among the largest in this sector and is the basis for studies related to the restoration of an eco-sustainable economy which would allow the development of marginal areas present throughout Southern Italy.